Development of a novel nutritional assessment model based on strontium and other compositional factors in apples across seven regions in China - Hong, Tiannuo; Zhao, Zhenyu; Bian, Wenbo; Zhu, Wenqi; Li, Ziqi; Shen, Guohui; Gu, Yanting; Chen, Lu; Guo, Yanzhi (Frontiers in Sustainable Food Systems, 2023)
In the aftermath of the Green Revolution's remarkable enhancement of global crop yields, particularly in rice and wheat, the focus on hunger has shifted from mere caloric sufficiency to addressing deficiencies in essential micronutrients. This transition highlights the concept of hidden hunger, where inadequate intake of vital nutrients persists despite access to an adequate number of calories. Among these crucial elements, strontium (Sr), an alkaline earth metal, plays a pivotal role in human physiology, notably in bone health and disease. Despite its significance, variations in Sr content across different regions, combined with diverse dietary habits, result in insufficient intake levels, particularly within China. This study aims to bridge this gap by integrating traditional sensory attributes and various nutritional parameters including Sr content for a comprehensive assessment of apples from major Chinese apple-producing regions. Through meticulous analysis and the establishment of characteristic indices, a novel apple quality evaluation system was developed that exemplifies a broader framework for evaluating agricultural products within China. This innovative approach not only enhances our understanding of agricultural product quality but also provides a practical solution to hidden hunger by ensuring informed consumer choices and improving nutritional intake. Furthermore, it serves as a valuable foundation for addressing deficiencies in essential micronutrients and advancing global efforts against hidden hunger.